Kabuki heroes on the Osaka stage, 1780-1830 - Gerstle, C. Andrew; Clark, Timothy; Yano, Akiko (Honolulu : University of Hawai'i Press, 2005)
"Kabuki Heroes is about collective participation in urban culture - on the stage, in poetry salons, in art studios and in fan clubs. Focusing on the culture of Kabuki theatre in Osaka and Kyoto, it illustrates the passionate hero worship of actors by all levels of society. Fans vigorously engaged in the creation of celebrity and fame for their idols, and thereby won their own moments of glory and glamour in the spotlight. Many of these participants are represented here - most of them ordinary townsmen, but also a few samurai and courtiers. This interactive nature of Kabuki culture is particularly intriguing: the actors themselves not only appeared on stage, but involved themselves in other cultural circles such as poetry salons. Kabuki fan clubs, on the other hand, performed formal rituals at the theatre, individual fans became amateur performers, while others created lavish colour prints and books to support favourite actors and spread their fame." "This catalogue illustrates that our obsession with celebrity is not just a modern phenomenon: in eighteenth- and nineteenth-century Osaka we can rediscover many elements in common with our own times. Most importantly, after the spread of new colour-woodblock printing technology in the late 1760s, a golden age of popular Kabuki culture was promoted far and wide with beautifully coloured prints and books. The fine examples brought together here from leading public and private collections in Europe and Japan evoke a fascinating period when theatre, art and poetry were essential elements of social and cultural life."--BOOK JACKET.
First published in United Kingdom by British Museum Press--T.p. verso.
Exhibition catalog.
Keywords: Color prints, Japanese -- Exhibitions; Kabuki -- Pictorial works; Kabuki in art -- Exhibitions; Actors -- Portraits